Impact Continuous Tiktok to Improve English Speaking Skills Through the Conversation Analytic Role-Play Method (Carm) - khaliatun mardiyah; Syafiul Anam; Him’mawan Adi Nugroho; Slamet Setiawan (Universitas Islam Negeri Palopo, 2025)
This research aims to examine the influence of intentions to use TikTok continuously on improving students' English speaking skills through the Conversation Analytic Role-Play (CARM) method. This research uses mixed methods, namely combining qualitative research with descriptive methods and quantitative research with experimental methods. The research results show that continued use of TikTok using the CARM method has a positive and significant impact on improving students' English speaking skills, compared to the control class who did not use TikTok. Apart from that, the research results also show that TikTok is seen favorably by students as a tool for learning English. Students feel learning English with TikTok is more fun, easier and effective. This research contributes to the development of innovative and creative English learning by utilizing the social media platform that is popular among generation Z, namely TikTok. This research also provides suggestions for teachers and researchers to further utilize TikTok's potential in English language learning, especially in improving students' speaking skills.